REVIEW : TINGKAT EFEKTIVITAS IMUNISASI CAMPAK DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN CAMPAK DI INDONESIA - Faizal Auladi Rivianto; Indah Laily Hilmi; Salman Salman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Measles is a disease caused by Morbillivirus measles virus which is an RNA virus from the Paramyxovirus group. This disease attacks the respiratory and immune systems of a person and is contagious. Measles is easy to recognize because it has characteristic clinical symptoms and has become a universal disease. This makes measles a concern of various countries because the disease can cause death if not treated and prevented from spreading. The purpose of this study is to analyze the factors that can influence the incidence of measles in Indonesia by using a literature study in the last 6 years (2016-2022). The method used is a literature review which includes the literature search process, exclusion inclusion criteria and study selection and literature quality assessment. The total literature used is 14 samples of research articles. The results showed that there were various factors that influenced the incidence of measles, but the dominant factors influencing the level of knowledge of parents regarding measles immunization and measles immunization status. It is hoped that the public will gain insight regarding measles immunization and understand how to prevent measles and maintain a clean environment so that it does not become a breeding ground for disease